Transformational Leadership and Career Development on Hospital Nurse Performance - Irfan Daud, Muhammad; Malik Assidik , Ramadhan; Kartono, Kartono (Publikasi Indonesia, 2024)
The purpose of this study is to determine the relationship between transformational leadership and career development on the performance of hospital employees. Hospitals are complex organizations that require effective leadership and appropriate career development to achieve optimal performance. This research focuses on the role of transformational leadership in improving hospital employee performance and how career development mediates the relationship between transformational leadership and hospital employee performance. This study involved 150 respondents who were nurses in hospitals. The research method used is a quantitative method with data collection through questionnaire distribution. The respondents of this study are hospital employees at various levels, ranging from medical staff to senior management. The results of this study make practical and theoretical contributions to the development of hospital management and provide recommendations to practitioners and policymakers to optimize the performance of hospital staff through the application of transformational leadership and effective career development.